Examining the Roles of Educational, Social and Psychological Factors in Financial Literacy: A Mediation Analysis - Adiandari, Ade Maharini; ., Amirusholihin; Nihaya, Ina Uswatun (Journal of Ecohumanism, 2024)
This research aims to identify and explain systematically and accurately the influence of preference for family and peers, preference for media, preference for education and mindfulness on financial literacy, as well as exploring the role of mindfulness as a mediating variable. The type of research used is explanatory research by explaining the influence and relationship between variables through hypothesis testing and analyzed using the PLS-SEM method approach. The population in the study was Indonesian people aged 17 years and over, sampling used quota sampling and a sample size of 990 respondents was obtained. Variable measurement is based on a 4 point gradation with an itemized rating scale. The research results show that there is an influence of preference of education on financial literacy. While preference for family and peers and preference for media are not proven to directly influence financial literacy, it is also proven that there is a need for a mindfulness variable to link these two variables. This means that psychological factors, such as mindfulness, can be a good mediation for increasing people's financial literacy.